Ptaquiloside from bracken (Pteridium spp.) promotes oral carcinogenesis initiated by HPV16 in transgenic mice. Issue 4 (29th March 2020) - Gil da Costa, Rui M.; Neto, Tiago; Estêvão, Diogo; Moutinho, Magda; Félix, Ana; Medeiros, Rui; Lopes, Carlos; Bastos, Margarida M. S. M.; Oliveira, Paula A.
Abstract : Bracken ( Pteridium spp.) is a common weed that is consumed as food especially in Asia, and is suspected of promoting carcinogenesis induced by papillomaviruses in the digestive and urinary systems. Abstract : Bracken ( Pteridium spp.) is a common weed that is consumed as food especially in Asia, and is suspected of promoting carcinogenesis induced by papillomaviruses in the digestive and urinary systems. This is particularly worrying because the incidence of head-and-neck cancers associated with the human papillomavirus (HPV) is rapidly increasing, and HPV co-carcinogens urgently need to be identified. This study tested the hypothesis that two bracken compounds, ptaquiloside and rutin, are able to promote head-and-neck and bladder carcinogenesis in HPV16-transgenic mice. Expression of HPV16 E6 and E7 in oral and bladder tissues was confirmed using quantitative real-time PCR. Mice were exposed orally to ptaquiloside (0.5 mg per animal per week for 10 weeks from 20 weeks-old) or rutin (413 mg kg −1 day −1 for 24 weeks from 6 weeks-old), sacrificed at 30 weeks-old and studied histologically. HPV16 E6 and E7 expression was higher in oral mucosa compared with the bladder ( p 0.001). Importantly, ptaquiloside, but not rutin, increased the incidence of oral squamous cell carcinomas ( p = 1.2 × 10 −8 ) in HPV16-transgenic mice. Also, cancers of unexposed transgenic mice were restricted to the tongue base, while ptaquiloside-exposed mice showed multifocal lesions throughout the oral cavity. Wild-type controls showed no oral lesions. No bladder lesions were observed in any treated or untreated group. These results indicate that ptaquiloside from bracken is able to promote oral carcinogenesis initiated by HPV16. Rutin did not show any carcinogenic effects in this model. The absence of bladder lesions may reflect an insufficient incubation period or factors related to the specific viral oncogenes present in this model.